TOURISM INDUSTRY DEVELOPMENT: DIGITALIZATION AND IMPLEMENTATION ASPECTS (Journal of Economic Research & Business Administration, 2019)
Tourism industry is one of the popular areas of economic development. Kazakhstan is a unique region in the world because of its history, geographical position, and size. According of this and the world trends of globalization the digitalization grows up very intensively. These factors have resulted in the country’s particular spaces where internet and mobile signals are either absent or digital technology usage is controlled. In addition, by employing critical discourse analysis of over 450 media texts produced between 2009 and 2017, the study reported the conceptual understanding of digital tourism, the ways the media representation has changed over time and explored the broad social context and debates in which the concept is embedded. This article examines the impact of digital development on the tourism industry. It also considers the advantages of information technology in the promotion of e-tourism. The development of e-tourism is connected with the fact that today’s world community cannot be imagined without a variety of portable technical means.